Crossing the River: Exploring the Geography of Irish Traditional Music - Kearney, Daithí (Journal of the Society for Musicology in Ireland, 2008)
Geographical interest in music has developed dramatically in the last decade. Musicology, and ethnomusicology in particular, is already intensely geographical. The two subjects can inform each other to create a better understanding of the role of music in society. In this article, the relationship between politics in the performance of music, particularly in consideration of national identity, is examined in an Irish context. Just as Irishness has become a global entity, Irish traditional music has become a global commodity. Attempts at constructing the narrative of Irish traditional music as an essentially Irish music is bound up in the institutionalization of Irish traditional music through local government, universities and organisations such as Comhaltas Ceoltóirí Éireann. Irish traditional music has rarely been independent of politics in the last two decades. It is a connection that has intensely geographical implications for the performance of Irish traditional music.